Effects of different salinity levels on rice production - Md. Sarwar, Jahan; Mohd Nozulaidi, Nordin; Mond Khairi, Che Lah (2015)
Background: Salinity is one of major problems for rice production. Objective: We tested if different salinity conditions affect production of local rice variety. Rice variety of MR219 was cultivated under different saline conditions and yield and plant parameters were evaluated. Results: Root and shoot length decreased gradually with increasing saline concentration in soil solution. Chlorophyll (Chl) content decreased under salinity condition than control but soil pH was unchanged except 6 ds salinity which significantly reduced soil pH. Relative water content (RWC) decreased with increasing salinity condition in soil solution. Plant height and tiller numbers also decreased with increasing salinity in soil. Other parameters, panicle length, panicle per pot, grain per plant and weight of grains showed similar to the plant height. Conclusion: These results suggest that local variety, MR219, is saline susceptible and need to pay attention in agronomic practices for sustainable crop production.